The Influence of Supply Chain Collaboration Strategies on Innovation Performance in the Pharmaceutical Industry: The Role of Supply Chain Competence and Absorptive Capacity on the Relationship - ALZAABI, NOURA MOHAMED (2022)
Embedded under the theory of dynamic capabilities, this study aims to identify how the pharmaceutical industry can achieve innovation performance using supply chain collaboration strategies, and how this relationship is affected by factors such as supply chain competence and absorptive capacity. The present study is underpinned by the dynamic capabilities’ theory as its primary guiding framework. Drawing on dynamic capabilities’ theory, the researcher embedded the present research under a positivist paradigm and adopted a deductive approach. In other words, the research was carried out using quantitative methodology whereby survey responses were collected from 351 pharmaceutical manufacturing industry members. Analysis of the data was carried out using Structured Equation Modelling (SEM) and revealed several key insights. The present research identifies that strategic relationship with supply chain partner is positively linked to innovation performance. In addition, supply chain competence mediates the relationship between supply chain collaboration strategies (strategic relationship with supply chain partner and supplier involvement in NPD) and innovation performance of the pharmaceutical manufacturing industry. It was also noted that supply chain competence was found to have a positive association with innovation performance. Furthermore, it was noted that the absorptive capacity does not impact the the relationship strength between supply chain collaboration strategies (strategic relationship with supply chain partner and supplier involvement in NPD) and innovation performance of the pharmaceutical manufacturing industry The study has bridged an essential gap in the theoretical field of dynamic capabilities theory as only few studies have been conducted linking supply chain and dynamic capabilities. Secondly, the research generates essential knowledge by identifying the indirect link between supply chain collaboration strategies, supply chain competence and innovation performance. Furthermore, the research makes a novel contribution in the field of supply chain competence. The research enables managers in the pharmaceutical industry to obtain a deeper understanding of the advantages of adopting certain beneficial supply chain collaboration strategies to improve innovation performance, through supply chain competence.